The Picture Book and its Role in Preschool Mathematics Education - Maričić, Sanja; Stakić, Mirjana (Revija za elementarno izobraževanje, 2023)
The paper examines the role of the picture book as a learning resource in preschool mathematics education and illustrates the possibilities for its application. The paper aims to examine whether preschool teachers use picture books in preschool mathematics education, what areas of mathematics they most use these for, and whether they recognize methodological advantages to their application. Results show that half of preschool teachers use the picture book as a teaching resource in preschool mathematics education, that it is mostly used to develop the concept of natural numbers and spatial relations, as well as that teachers clearly perceive methodological advantages.